A NEEDS ANALYSIS FOR DESIGNING A MODULE-BASED AUTOMATED WRITING EVALUATION (AWE) TOOL IN INDONESIAN EFL ACADEMIC WRITING - Marhamah; Hendri Yawan; Litha Nesidekawati Dakka (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2026)
Marhamah1, Hendri Yawan2, Litha Nesidekawati Dakka3 1,2,3 Universitas Sembilanbelas November Kolaka, Indonesia Marhamahudri@gmail.com Received: May 30, 2025 Revised:  June  27, 2025 Accepted: August 16, 2025   ABSTRACT The growing use of AI Automated Writing Evaluation (AWE) tools in higher education has raised concerns about students’ reliance, lack of critical engagement, and ethical uncertainties. However, limited research has examined how AI-supported writing is experienced in Indonesian EFL higher education contexts, particularly regarding its pedagogical and ethical implications in academic writing classrooms. This study, as part of a broader Design-Based Research (DBR) project, focused on a needs analysis through a qualitative case study to explore students’ and lecture’s perceptions of AI-supported academic writing in an Indonesian EFL context and to inform the design of a digital writing module. Data were collected through interviews with one instructor, focus group discussions with 15 students, and the analysis of student writing drafts. Reflexive thematic analysis was applied to capture patterned meanings and interpretive insights. Findings showed that while AI tools improved grammatical accuracy and text coherence, they often encouraged limited argumentation, homogenized structures, and confusion about academic integrity. These results suggest the importance of embedding scaffolding for reflection, feedback literacy, and digital ethics into instructional design.